An in silico planning study comparing doses and estimated risk of toxicity in 3D-CRT, IMRT and proton beam therapy of patients with thymic tumours. (April 2019) - Lideståhl, Anders; Mondlane, Gracinda; Gubanski, Michael; Lind, Pehr A.; Siegbahn, Albert
Highlights: Dose distributions was compared between SFUD, 3D-CRT and IMRT in pts with thymic tumours. NTCP for different endpoints was calculated and compared between plans. SFUD was associated with significantly lower doses to organs at risk. The risk of toxicity was reduced with SFUD for several endpoints. Abstract: Purpose: To compare the dose distributions produced in patients (pts) treated for thymic tumours with spot-scanning proton beam therapy (PBT) implemented with single-field uniform dose (SFUD), intensity-modulated radiation therapy (IMRT) and three-dimensional conformal photon-beam based radiotherapy (3D-CRT). Methods: Twelve pts, treated with 3D-CRT, were included. Alternative IMRT and SFUD plans were constructed. The IMRT plans were created using a setup with beams incident from 5 to 6 different angles. For the SFUD plans, a field-specific planning target volume (PTV) was created for each patient and a clinical target volume (CTV)-based robust optimization was performed. A robustness evaluation was performed for the CTV for all SFUD plans. A dosimetric evaluation was conducted for the doses to the CTV and organs at risk (OARs) for all plans. The normal tissue complication probability (NTCP), for different endpoints, was calculated using the Lyman-Kutcher-Burman (LKB)-model and compared between plans. Results: SFUD was associated with significantly lower mean doses to the oesophagus, the heart, the left anterior descending coronary artery (LAD), lungs and breasts compared to 3D-CRT and IMRT. The maximum dose given to the spinal cord was significantly lower with SFUD. The risks for pneumonitis, esophagitis and myelopathy were significantly reduced in the SFUD plans. Conclusions: The present study showed dosimetric advantages of using scanned-beam PBT for the treatment of thymic tumours, as compared to 3D-CRT and IMRT, especially in regard to lower doses to the oesophagus and lungs. The risk of toxicity was reduced with SFUD.